Understanding regulation of HIV-1 protease precursor autoprocessing - Tien, Chih-Feng, author; Chen, Chaoping, advisor; Bamburg, James, committee member; Peersen, Olve, committee member; Quackenbush, Sandra, committee member (Colorado State University. Libraries, 2019)
The HIV-1 protease (PR) is initially synthesized as part of the Gag-Pol polyprotein precursor in the infected cell. Protease autoprocessing is generally referred to proteolytic reactions catalyzed by the precursor itself leading to liberation of free, mature PR in a highly regulated manner. We study the precursor autoprocessing mechanism using engineered fusion precursors carrying the p6*-PR miniprecursor sandwiched between various proteins and/or epitope peptides expressed in transfected mammalian cells. The studies reported here examined and identified factors involved in regulation of precursor autoprocessing. Modulation of precursor autoprocessing activity and outcomes by the 26 amino acid maltose binding protein signal peptide (SigP) mimicking the proviral constructs. A H69D mutation in PR abolished autoprocessing of SigP-containing fusion precursors or Gag processing in viral particles whereas it only partially suppressed autoprocessing of fusion precursors lacking SigP. The mature PRs released from SigP-carrying precursors or associated with the viral particles are both resistant to self-degradation whereas those released from SigP-lacking fusion precursors are prone to self-degradation. Furthermore, the PR-containing autoprocessing intermediate fragments released from a SigP fusion precursor or a proviral constructs showed protease inhibitor response profiles distinct to those released from the corresponding fusion precursor lacking SigP. These findings of context-dependent modulation reveals the complexity of precursor autoprocessing regulation that most likely accompanies sequence variation imposed by the evolution of the upstream Gag moiety. We also examined trans proteolysis for its functional correlation with precursor dimerization. Fusion enzymes carrying GST, a well-known dimer forming protein, processed the GST-fused substrate in trans as expected. Interestingly, positive trans processing was also detected between enzyme and substrate precursors carrying maltose binding protein (MBP), a known monomeric tag, or lacking any dimer-inducing tag, suggesting that a dimer-inducing flanking tag is not required for trans proteolysis in the transfected cells. Sucrose gradient sedimentation analysis detected dimeric substrates, with or without dimer-inducing GST, as the major complexes in transfected cell lysates. In the presence of a protease inhibitor (PI) at high enough concentrations, dimeric enzymes were predominantly detected. Without PI treatment, fusion enzymes with different tags and varied p6* sequences showed monomers or dimers or mixtures, suggesting modulation of enzyme dimerization by p6* peptides and flanking tags. Precursors carrying two PRs in tandem tethered by a GGS linker demonstrated higher propensities of forming inter-molecular dimers than intra-molecular dimers, indicating a role of p6* peptide in regulating precursor dimerization. Collectively, our results decoupled the requirement of a dimer-inducing tag upstream of the p6*-PR miniprecursor for precursor trans proteolysis and demonstrated elements within and beyond p6*-PR miniprecursor that collectively influence precursor dimerization, which revealed additional complexity involved in precursor autoprocessing regulation. In summary, this dissertation highlights complicated regulations and more than one productive pathway involved in HIV-1 protease precursor autoprocessing.
Keywords: HIV-1; protease inhibitor; trans cleavage; precursor autoprocessing; dimerization; protease precursor